Teratogenicity test of chlorotalonil containing fungicide formulation (BRAVO 500) and copper sulphate in chicken embryos after single and simultaneous administration - Budai, Péter; Szabó, Rita; Kormos, Éva; Lehel, József (Acta Agraria Kaposváriensis, 2012)
The aim of this study was to determine the individual and combined toxic effects of BRAVO 500 fungicide (40% chlorotalonil) and copper sulphate on the development of chicken embryos. On the first day of incubation chicken eggs were dipped in the solution or emulsion of the test materials for 30 minutes. Applied concentration of copper sulphate was 0.01% and of fungicide BRAVO 500 were 1% and 10%. The chicken embryos were examined for the followings: rate of embryo mortality, body weight, type of developmental anomalies, macroscopic examination. Our teratogenicity study revealed that, the combined administration of copper sulphate and chlorotalonil containing fungicide formulation (BRAVO 500) caused a significant reduction in the body weight of embryos and increased the rate of embryonic mortality. The joint toxic effect of copper sulphate and BRAVO 500 is an additive effect compared to the individual toxicity of the test materials.
Keywords: chlorotalonil; copper sulphate; interaction; ecotoxicology; chicken embryo